2010
DOI: 10.1103/physrevd.81.099902
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Hyperfine splittings in bottomonium and theBq(q=n,s,c)mesons [Phys. Rev. D81, 071502 (2010)]

Abstract: A universal description of the hyperfine splittings (HFS) in bottomonium and the Bq (q = n, s, c) mesons is obtained with a universal strong coupling constant αs(µ) = 0.305(2) in a spin-spin potential. Other characteristics are calculated within the Field Correlator Method, taking the freezing value of the strong coupling independent of n f

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…The latter HF splitting was predicted in Ref. [27], if a ''universal'' coupling HF ¼ 0:31 is used in the HF potential.…”
Section: Introductionmentioning
confidence: 73%
“…The latter HF splitting was predicted in Ref. [27], if a ''universal'' coupling HF ¼ 0:31 is used in the HF potential.…”
Section: Introductionmentioning
confidence: 73%
“…A comparison of the data with various model results is presented in the concluding section of this paper. This large hyperfine splitting has recently been investigated as a possible indicator of new physics [8], as a means of adjusting the value of the strong coupling parameter [9], and to fix the value of α S in an investigation other quarkonium states [10]. While further data should clarify these points, in this paper we investigate whether the model we employed in our 2007 paper [11], is robust enough to accommodate this new data.…”
Section: Introductionmentioning
confidence: 84%
“…Given the numerous approaches to the calculation of the bb hyperfine splittings, including the delta function approach of Ref. [10], our perturbative treatment is relevant to the overall discussion of the Υ (nS) − η b (nS) mass difference.…”
Section: Heavy Quarkonium Hyperfine Potentialmentioning
confidence: 99%
“…Lattice QCD Gray et al [9] 61 ± 14 30 ± 19 Meinel [10] 60.3 ± 7.7 † 23.5 ± 4.7 † Meinel [10] 28.0 ± 4.2 ‡ Dowdall et al [11] 70 ± 9 35 ± 3 ‡ Lewis and Woloshyn [12,13] 56 ± 1 24 ± 3 Burch and Ehmann [14] 37 ± 11 13 ± 26 Burch and Ehmann [14] 71 ± 8⋄ 27 ± 17⋄ Potential models and related Badalian et al [15] 64.2 ± 0.4 36 ± 2 Badalian et al [15] 70.0 ± 0.4 36 ± 2 Badalian et al [16] 63.4 36 ± 2 Badalian et al [16] 71 1S splitting. As discussed previously, recent experiments [1,2,6] all measure a smaller value for the 1S splitting, which would imply that these lattice predictions are overestimates.…”
Section: Lattice Qcdmentioning
confidence: 99%
“…All of the models which postdate the discovery of the η b (1S) [15,16,28,37,46,48] are fit to the earlier 1S splittings measured at BaBar [3,5] and CLEO [4], or to the PDG averages at the time, and do not take account of the more recent, smaller values of Belle [2,6] and Dobbs et al [1] shown in Table I. Each of these models also predicts a 2S splitting somewhat larger than that observed at Belle.…”
Section: Potential Models and Relatedmentioning
confidence: 99%